Development and characterization of foam mat dried palmyrah fruit pulp powder - Vengaiah, P.C.; Kaleemullah, S.; Madhava, M.; Srikanth, A.D. (Journal of Plantation Crops, 2024)
The Palmyra fruit is a good source of vitamin C, carotenoids, minerals, and sugars and the fruit pulp is used to treat skin problems, nausea, vomiting and improves digestion by relieving constipation. Study was conducted to optimize the process parameters for the production of palmyrah fruit pulp powder using foam-mat drying. Palmyrah fruit pulp was foamed by incorporating egg albumin (EA) (0, 5, 10, 15 and 20 %, w/w) and methyl cellulose (MC) (0, 0.25, 0.5, 0.75 and 1 %, w/w) as foaming agents with different pulp concentrations (PC) (8, 10, 12, 14 and16 °Brix) and various whipping times (WT) (1, 2, 3, 4 and 5 min) using response surface methodology with CCRD design. From the results, the optimum conditions achieved after the numerical and graphical optimization for maximum foam expansion and stability were: EA (6.875 g/100 g pulp), MC (0.262 g/100 g pulp), PC (14° Brix), and WT (2 min). The drying time required for foamed palmyrah pulp was lower than non-foamed pulp. The quality attributes of palmyrah fruit pulp powder obtained from the pulp of 14°Brix added with 6.875 % egg albumin and methyl cellulose of 0.262% whipped for 2 min and dried with a foam thickness of 4 mm at a temperature of 60 °C was found to be optimum to produce the foam-mat dried powder.